Local corrosion mechanism of an Al-Zn-Mg-Cu alloy in oxygenated chloride solution: Cathode activity of quenching-induced η precipitates. (October 2021) - Chen, Mingyang; Zheng, Xu; He, Kezhun; Liu, Shengdan; Zhang, Yong
Graphical abstract: Highlights: Quenching-induced η phase has higher potential than ageing-induced η phase. Quenching-induced η phase acts as a cathode to trigger corrosion. Corrosion pits change into reticular morphology due to slow quenching. Depletion of Zn and Mg atoms improves corrosion resistance of PFZ after ageing. Abstract: The specific corrosion behavior of quenching-induced η precipitate is usually ignored. In this work, the corrosion initiation and propagation of Al-Zn-Mg-Cu alloy after different quenching rates and ageing are studied by quasi-in-situ corrosion and microchemical analysis. The quenching-induced precipitates act as cathodes to trigger corrosion, and the morphology changes from deep pit-like into reticular intergranular corrosion with the quenching rate decreasing. After artificial ageing, Zn and Mg atoms in solute-depletion zone are consumed and migrate into quenching-induced precipitates or form ageing-induced precipitates. This enhances the potential of precipitation-free zone and improves the corrosion resistance of aged samples.